Strategi Pengembangan Usaha Kelapa Sawit Plasma Dan Mandiri Di Desa Kakullasan Kecamatan Tommo Kabupaten Mamuju - Bongga, Alfrian; Sheyoputri, Aylee Christine Alamsyah; Azuz, Faidah (PALLANGGA: Journal of Agriculture Science and Research, 2025)
This study aims to determine the strategy in developing plasma and independent scheme oil palm businesses in Kakullasan Village, Tommo District, Mamuju Regency. Oil palm is one of the leading commodities that contributes to the regional economy and farmer welfare. This study uses a descriptive method with primary data collection through questionnaires, interviews, and observations and secondary data through government agencies. The population in this study were 25 oil palm farmers. Plasma farmers numbered 10 people, independent farmers numbered 13 people, and P+M numbered 3 people. The results of this study indicate that farmers who carry out extensification are plasma farmers with an average land area of plasma farmers that is larger than independent farmers; then plasma farmers become mixed farmers, namely independent plasma with an average land area of plasma farmers of 3 Ha; while independent farmers are 2.7 Ha and mixed plasma and independent farmers with an average land area of 4.8 Ha. Therefore, farmers who tend to do extensification are plasma farmers compared to independent farmers. Farmers who tend to do extensification will find it easier to increase their palm oil production because they are supported by a larger land area. Penelitian bertujuan untk mengetahui strategi dalam mengembangkan usaha kelapa sawit skema plasma dan skema mandiri di Desa Kakullasan, Kecamatan Tommo, kabupaten Mamuju. Kelapa sawit adalah salah satu komoditas unggulan yang berkontribusi terhadap perekonomian daerah dan kesejahteraan petani. Penelitian ini menggunakan metode deskriptif dengan pengumpulan data primer melalui kuesioner, wawancara, dan observasi serta data sekunder melalui instansi pemerintah. Populasi dalam penelitian ini adalah petani sawit yang berjumlah 25 orang petani. Petani plasma berjumlah 10 orang, petani mandiri berjumlah 13 orang, dan P+M berjumlah 3 orang. Hasil penelitian ini menunjukkan bahwa petani yang melakukan ekstensifikasi adalah petani plasma dengan rata-rata luas lahan petani plasma yang lebih banyak dibandingkan petani mandiri; kemudian petani plasma menjadi petani campuran yaitu plasma mandiri dengan luas lahan rata-rata petani plasma yaitu 3 Ha; sedangkan petani mandiri 2,7 Ha dan petani campuran plasma dan mandiri dengan luas lahan rata-rata yaitu 4,8 Ha. Oleh karena itu, petani yang cenderung melakukan ekstensifikasi yaitu petani plasma di banding petani mandiri. Petani yang cenderung melakukan ekstensifikasi akan lebih mudah dalam meningkatkan produksi kelapa sawitnya karena didukung luas lahan yang lebih besar.